Regulatory Talk About Climate Policies: National Plans or Commission Streamlining - Simon Fink (JCMS: Journal of Common Market Studies, 2025)
National energy and climate plans (NECPs) are a cornerstone of European Union (EU) climate policy. As `hard' soft governance instruments, NECPs allow comparison of member state policies and monitoring of whether they reach EU aims. My argument is that NECPs can be analysed as regulatory talk, with both member states and the Commission using reputational strategies—performative, technical, procedural and moral—to lend authority to their policy descriptions and projections. I show that the technical rhetoric of draft NECPs varies according to domestic capacities. Commission comments are uniform, emphasising performance. Member states do not adapt their final NECPs to the regulatory talk of the Commission. They use the same reputational mix as in the draft NECPs. In sum, the NECPs portray an output-oriented legitimation strategy, emphasising performance and technical proficiency. The actor bases of the found national variation of regulatory talk and its effects are questions for further research.
Keywords: 330; climate policy; organisational reputation; public policy; regulatory talk; soft governance